Ghantasamvarna variety of the Shikhara of the Shiva Temple - Temples of India Project Team (Jio Institute, 2024)
Closer view of the shikhara (superstructure) of the mandapa (pillared hall) of the Shiva temple. This shikhara is of the ghantasamvarna (bell roof) variety of a pyramidical nature. It is made up of several small ghantikas (bells) that have chaitya dormer motifs on their pedestals. These aedicules are arranged in such a manner that they appear cascading from top to bottom.